А LASER-PHOTOMETRIC OBSERVATIONAL COMPLEX OF THE ODESSA ASTRONOMIOAL OBSERVATORY - Medvedev, Yu. A.; Dobrovolsky, A. V.; Paltsev, N. G.; Chaichuk, R. A. (Одеські астрономічні публікації, 2017)
The creation of a laser photometric complex for АЕS observations, which enters into the net 0$ laser-location АЕS observations on the territory of the Ukraine, nears completion at Kryzhanovka Station of the Odessa Astronomical Observatory. The station is equipped to meet high standards and permits successfully carrying out works within the frames 0$ international projects.